Syekh Hasan Yamani Islamic Boarding School and Its Development (1980-2024) - Aqeel Nebras; M. Rasyid Ridha; Ahmadin Ahmadin; Bakhtiar Bakhtiar (Journal of General Education and Humanities, 2026)
Pesantren is a distinctive Islamic educational institution in Indonesia that functions not only as a center for transmitting religious knowledge but also as a medium for internalizing values, shaping character, and strengthening social life. This study examines the history of Pondok Pesantren Syekh Hasan Yamani and its influence on Islamic education in West Sulawesi, focusing on its establishment, development, and contributions to the region. This research uses a qualitative approach with a historical perspective, applying methods such as heuristics, source criticism, interpretation, and historiography. Data were collected through literature review, field observations, interviews with pesantren leaders, teachers, alumni, and community figures, as well as document analysis. This approach enables a systematic reconstruction of the pesantren’s historical development and its social-religious significance. The findings reveal that Pondok Pesantren Syekh Hasan Yamani was established in 1980 under the leadership of KH. Muh. Said Al-Mahdaly, continuing earlier da‘wah activities through religious gatherings and majelis taklim. Over time, the pesantren has adapted to societal changes while maintaining its traditional Islamic values. Its contributions are reflected in strengthening religious education, fostering students’ moral character, and serving as a center for da‘wah and community empowerment. Thus, the pesantren plays a strategic role in developing Islamic education and reinforcing Islamic identity in West Sulawesi.